2021
DOI: 10.1007/s12186-021-09275-3
|View full text |Cite
|
Sign up to set email alerts
|

Learning or Leaving? Individual and Environmental Factors Related to Job Satisfaction and Turnover Intention

Abstract: In addition to well-being, workplace learning has gained increasing interest in supporting employee and organizational development and success. Focusing on specific factors affecting workplace learning and well-being, this study examines the links between individual factors (basic psychological need satisfaction) and environmental factors (expansiveness of the workplace as a learning environment), job satisfaction, and turnover intention. Survey data were collected from the employees (N = 153) of two Finnish e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 75 publications
1
18
0
Order By: Relevance
“…This means that the lower the job satisfaction felt by employees, the higher the employee's intention to leave the company (turnover intention). These results are in line with several previous studies (Machado et al, 2018;Park & Min, 2020;Wang et al, 2020;Puhakka et al, 2021). Job dissatisfaction experienced by individuals causes many negative effects that will occur on individuals, such as reduced willingness to work, poor work performance, delays, and increased desire to leave the company (Chen & Wang, 2019).…”
Section: Job Satisfaction On Turnover Intentionsupporting
confidence: 92%
“…This means that the lower the job satisfaction felt by employees, the higher the employee's intention to leave the company (turnover intention). These results are in line with several previous studies (Machado et al, 2018;Park & Min, 2020;Wang et al, 2020;Puhakka et al, 2021). Job dissatisfaction experienced by individuals causes many negative effects that will occur on individuals, such as reduced willingness to work, poor work performance, delays, and increased desire to leave the company (Chen & Wang, 2019).…”
Section: Job Satisfaction On Turnover Intentionsupporting
confidence: 92%
“…The trainers and training managers highlighted the importance of both formal and informal learning as the most effective tools for staying at the cutting edge of lifelong learning. Puhakka et al (2021) and Cerasoli et al (2018) indicate the wide variety in formal and especially informal learning activities in the workplace; the workplace itself (Segers et al , 2021) is also a complex site for learning. Accordingly, within the workplace the interviewees described individual and socially shared informal learning activities: for instance, talking with colleagues, asking for feedback or conversating intentionally or spontaneously.…”
Section: Discussionmentioning
confidence: 99%
“…These learning conditions are usually divided into facilitating and inhabiting factors that relate to the work environment, resources and interpersonal structure at work. These can be summarized as contextual factors (Puhakka et al , 2021). Skule (2004) identifies three major components of the conditions relevant to learning in the workplace.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research on the relationship between job satisfaction and turnover intention has been described by several previous studies. For example, Khan & Aleem (2014); Puhakka et al, (2021) revealed that job satisfaction has a significant effect on employee turnover intention. This finding is also supported by Alam & Asim (2019) explains that high job satisfaction can reduce the level of employee desire to leave their job.…”
Section: Job Satisfaction and Turnover Intentionmentioning
confidence: 99%